Prosedur Penggunaan Dokumen Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) sebagai Syarat Administrasi Peralihan Sertipikat Hak Milik (SHM) Perorangan di Kantor Pertanahan Bandar Lampung - Anisa Nur Asyifa; Ratna Septiyanti (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study analyzes the use of the Land and Building Rights Acquisition Duty (BPHTB) documents as part of the administrative requirements in the registration of the transfer of Individual Ownership Certificates (SHM) at the Land Office of Bandar Lampung City. The aim of this study is to identify the stages of the process as well as to assess the functions and issues that arise. The method used is descriptive qualitative, with primary data collection techniques through in-depth interviews with officials and practitioners, direct observation of service processes, as well as secondary data analysis from official documents. The main findings of the study indicate that the procedures are carried out in accordance with existing However, in the field there are still challenges such as data mismatches, incomplete or non-standard documents, as well as problems with application systems. In conclusion, improving coordination between agencies and optimizing systems is very necessary to increase efficiency in land rights transfer services, which can have a positive impact on local policies.regulations, starting from the deed by the Land Deed Official (PPAT), examination at the counter, to the verification process, where BPHTB plays an important role as an indispensable requirement.